LACTARAN SESQUITERPEN VELLERAL DARI KULIT BATANG TUMBUHAN DRYMIS BECCARIANA GIBBS. (WINTERACEAE) YANG BERSIFAT SITOTOKSIK DAN ANTIMIKROBA - Bimo Budi Santoso; Darma Santi; Markus H. Langsa; Rina Mogea (FMIPA Universitas Papua, 2009)
Isolation guided by brine-shrimp ( Artemia salina) bioassay from the stem bark of .D. beccariana Gibbs. led to isolate a bioactive compound called Velleral (1) ((3aS,8aS)-2,2,8-trimethyl-3,3a.6.8a-tetrahydro-1H-azulene-5,6-dicarbaldehyde).The structure of this compound was elucidated based on physical and spectroscopic data (UV, IR, , 1H NMR, 13C-NMR and GC-MS). This compound showed significant active in the Artemia salina bioassay with IC50 2.92 µg/mL and exhibited siginificant cytotoxicity against murine P-388 leukemia cells with IC50 3,39 μg /mL.Moreover, the compound exhibited antibacterial and antifungal activity especially against Staphyloccocus aureus ATCC 25923 and Candida albians respectively. This result indicates that stem bark of D. beccariana is a potential source of bioactive compounds.